On the relationship between the “default mode network” and the “social brain” - Mars, Rogier B.; Neubert, Franz-Xaver; Noonan, MaryAnn P.; Sallet, Jerome; Toni, Ivan; Rushworth, Matthew F. (Frontiers in Human Neuroscience, 2012)
The default mode network (DMN) of the brain consists of areas that are typically more active during rest than during active task performance. Recently however, this network has been shown to be activated by certain types of tasks. Social cognition, particularly higher-order tasks such as attributing mental states to others, has been suggested to activate a network of areas at least partly overlapping with the DMN. Here, we explore this claim, drawing on evidence from meta-analyses of functional MRI data and studies investigating the structural and functional connectivity of the social brain. Finally, we discuss recent evidence for the existence of a DMN in non-human primates and evidence for its involvement in mediating social abilities. We end by discussing some of the implications of these observations.